As representações sociais da soropositividade para HIV e sua relação com a adesão ao tratamento - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The World Public Health has been facing great challenges nowadays; one of them is the controlling of the AIDS epidemic in Brazil and in the world. Such control could be established by the adherence to the antiretroviral therapy (ART), one of the biggest difficulties encountered by people living with HIV/AIDS (PLWHA). In this way, this article intends to conduct a quantitative research to understand the social representations (RS) of HIV-positive people and how it influences their process of adhering, or not, to antiretroviral therapy (ART). As for its specific objects, this paper seeks to better understand the social representations of the HIV status for young people living with HIV; to discuss the impact of these social representations in the adherence, or not, to antiretroviral therapy and analyze the possible relations between the HIV social representations, self-care practices and local socioculture. Regarding methodological procedures, the semi-structured interview with saturation of the dada has been used, and, therefore, 14 participants were selected under the inclusion/exclusion criteria. The collected data were analyzed through Bardin’s Contents Analysis technique. For its results, five final categories were defined, being: (i) HIV permeated by the vulnerability process; (ii): HIV through the transmission and prevention perspective; (iii) HIV regarding its discrimination and concealment; (iv): The process of adhering to therapies in the everyday life of people living with HIV and (v): The daily endurances experienced by people living with HIV. The HIV/AIDS representations surpass the intense daily living of distress (the daily experiencing of emotions such as guilt, fear and anguish) due to social stigmas resulting from prejudice. The second category pointed towards male gender issues, which influence men to behave in unhealthy manners, from which originates the diagnosis. The third core showed that HIV-positive people bear double suffering: the first comes from a physical point of view, with all the difficulties that accompany the condition and the ART’s side effects; and a second suffering, which is related to the social constructions of the disease, the latter being able to make itself vividly present in a seropositive person’s life. PLWHA go through various adversities due to social stigma, and, they do get in the way of their relationships, whether they are private (such as in affective relationships) or social (such as labor relationships) and one of the main strategies to face these setbacks is to hide and conceal their HIV status. The fourth core showed the difficulties in adhering to the ART, which encompassed the struggles in adjusting to the medicine, their side collateral effects, change of habits and mental health issues, even though ART represented a way to prolong the life of the participants. The fifth core was marked by representations of AIDS and death, but also by bringing empowerment to the individuals and a way to restart their lives. The conclusion is that the SR here described directly influence in the decision of adhering or not, or even inadequately adhering, to the ART, which has implications on the lives of the individuals.
Keywords: Representação Social; HIV; AIDS; HSH; Adesão; Terapia antiretroviral; Social representation; Adherence; Antiretroviral therapy; CIÊNCIAS HUMANAS: PSICOLOGIA